Designing a Simple Test to Measure and Rate Lubricant-Controlled Friction Reduction. Issue 6 (25th October 2022) - Ingram, M.; Roots, I.; Welham, T.; Smeeth, M.; Hamer, C.
Abstract: The ability of a lubricant to reduce friction and increase machine efficiency is one of its main functions. However, a standardized test to measure the ability of a lubricant to reduce friction does not exist. In this work we take a common tribometer and design a test sequence to allow the friction reduction of any lubricant to be measured and rated, quickly and accurately. The kinematic viscosity values at 40 and 100 °C for the lubricant, along with the density, are used to calculate appropriate entrainment speeds to maintain a constant test severity for each lubricant. A set sliding distance is determined experimentally to ensure that the metal surfaces are run in and that a stable tribofilm is formed at both temperatures. The lubricants are then rated in terms of their ability to maintain low friction in the boundary, mixed, and full film regimes. The proposed method has been designed ensuring good repeatability, across a range of common lubricants (engine oils, transmission fluids, hydraulic fluids, gear oils). This new method simplifies friction measurement and rating of lubricants using Stribeck curves, supporting the development and qualification of new lubricants.